A study on impulse buying behaviour of european tourists at airport environment KKIA Terminal 1 / Harijah Bakar - Bakar, Harijah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
This study examines the relationship between factors that influencing impulse buying behavior of European tourist in airport environment. The contribution of retailing to total airport revenue is becoming more important. In this study, will examines the relationship of passengers' impulse buying, impulse buying tendency, shopping motivation, money available and time available in the airport environment. The sample of data will collected at Kota Kinabalu International Airport (KKIA), Terminal 1. The limitations is to focus on impulse purchase behavior of European tourist and specifically on Airport environment. Here research limit only in Kota Kinabalu International Airport Terminal 1. Focus group are European Passenger. 100 Questionnaire are distributed to Focus Group within two weeks directly and SPSS 20.0 version are using to analyze data. This study searching the relationship of Impulse buying tendency, shopping motivation, money available and time available as factors that affect impulse buying behavior as dependent variable.